Global research on air pollution between 2005 and 2014: a bibliometric study. Issue 3 (4th July 2016) - Kolle, Shankar Reddy; Thyavanahalli, Shankarappa H.
Abstract : Purpose: The purpose of this paper is to analyze research works on air pollution published in 2005-2014 and indexed in Web of Science Core Collection. Design/methodology/approach: The data of research publications on "air pollution" from the Web of Science Core Collection database were collected with following search strategy: publications with terms "Air contaminat*", "Air pollut*", "pollut* air" or "contaminat* air" in their titles for the period of 2005-2014 were collected. A total of 4, 424 articles were published on air pollution during the period of 2005-2014, and the data were used for creation of database in Microsoft Excel for the analysis purpose. Bibliometric analysis techniques were applied wherever necessary. Findings: Out of 4, 424 articles published on air pollution in different languages, 4, 276 articles were in English. The years 2013 and 2014 showed rapid increase in number of articles published, 563 and 638, respectively. The increased number of articles resulted in an increase in number of pages published and references cited in the articles. The articles published in the year 2006 had received more number of citations (12, 318), and the average citation per article for the period was 17.59. Environmental Science was the major Web of Science subject category under which a greater number of articles were published. Article entitled as "Health effects of fine particulate air pollution: Lines that connect", published in Journal of The Air & Waste Management Association by Pope and Dockery (2006), was the highest cited article (1, 743) for the period, and the top most active journals that published huge number of articles were Atmospheric Environment and Environmental Health Perspective, with 11.79 per cent of the total articles (4, 424) published. Research limitations/implications: The findings of the study are limited to the journals covered under Web of Science Core Collection database and articles having the following keywords in their titles: "Air contaminat*", "Air pollut*", "pollut* air" or "contaminat* air". Originality/value: This study would be useful to researchers and policy makers to get an insight into the research trends of air pollution for effective decision-making and formulation of new research proposals.